(untitled) (Ustozlar uchun, 2025)
This article explores the neurological mechanisms that make active recall the gold standard of learning, including the "Testing Effect" and the role of the hippocampus in memory consolidation. By shifting from a receptive to a generative study model, learners can move beyond mere recognition to achieve true intellectual mastery and durable memory.